2013
DOI: 10.1017/s0025315413000878
|View full text |Cite
|
Sign up to set email alerts
|

Coral tissue mortality of the coral Cladocora caespitosa caused by gastropod Coralliophila meyendorffi in the Mljet National Park (eastern Adriatic Sea)

Abstract: The corallivorous gastropod Coralliophila meyendorffi (family Coralliophilidae) is a well-known predator of the coral Cladocora caespitosa, particularly in the eastern Adriatic Sea, where population outbreaks can drastically reduce coral cover. Coralliophila meyendorffi ranges in size from 5 to 40 mm in shell total length, and smaller specimens are often found living with the coral C. caespitosa. Specimens of C. meyendorffi feed exclusively on live coral tissue, stripping it from the calcium carbonate skeleton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…C. caespitosa is a species well adapted to the seasonal seawater temperature fluctuation in Mediterranean Sea (Kružić et al, 2013). However, C. caespitosa cannot well resist to an important increase of seawater temperature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…C. caespitosa is a species well adapted to the seasonal seawater temperature fluctuation in Mediterranean Sea (Kružić et al, 2013). However, C. caespitosa cannot well resist to an important increase of seawater temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Another important mass mortality event happened during the summer 2003 where C. caespitosa suffered of extensive tissue losses due to an exceptional warming episode (Garrabou et al, 2009; Kersting et al, 2013a). Several other mass mortality events happened afterwards as e.g., in the eastern Adriatic Sea in 2010 (Kružić et al, 2013) or in summer-autumn 2012 in the Levantine Sea (Cyprus) (Jiménez et al, 2014). Additionally, Kersting et al (2013a) observed several mass mortalities of C. caespitosa in the Columbretes Islands (north-western Mediterranean, Spain) from 2002 to 2012 due to water thermal anomalies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Mediterranean Sea, Cladocora caespitosa (a shallow-water zooxanthellate scleractinian coral), Lophelia pertusa and Madrepora oculata (a deep-water azooxanthellate scleractinian corals) are recognized as the main bioconstructors (see Kružic 2014). The fauna associated with these species has been the subject of some research (Koukouras et al 1998, Antoniadou & Chintiroglou 2010, Mastrototaro et al 2010, Calcinai et al 2013, Kružic et al 2013; however, none of these studies have assessed the spatiotemporal variability of the macro faunal assemblages associated with temperate corals.…”
Section: Introductionmentioning
confidence: 99%